STUDY OF THE SOCIAL AND ECONOMIC STRUCTURE OF CHILD LABOUR: WITH SPECIAL REFERENCE TO SHOE INDUSTRY IN AGRA DISTRICT - Singh, Rajesh; Verma, Sarita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of this study is to examine in depth the social and economic structure of child labour with reference to shoe industry in Agra district. Child labour is a social abuse which seriously affects the development and future of children. This research analyses the economic and social reasons which force children to work. Child labour is common in the shoe industry in Agra district where they have to work under difficult conditions. The study used data obtained from interviews with local workers, industry owners and officials. The findings suggest that poverty, lack of education and absence of effective policies promote child labour. Child labour is a serious social abuse which affects the future of children especially in developing countries. Through this research an attempt has been made to find out how economic and social factors force children to work.